Addressing medically underserved populations through maternal-fetal transport: a geographic analysis. (1st September 2020) - Rosenbloom, Joshua I.; Nelson, D. Michael; Saunders, Scott; Cole, F. Sessions; Chandarlis, Janet; Macones, George A.; Cahill, Alison G.
Abstract: Objective: Despite regionalization of maternal care in the USA, there is little contemporary information on characteristics and utilization of maternal–fetal transport. We used geographic analysis to investigate referral and transportation patterns of the maternal–fetal transport service at our institution. Methods: This is a retrospective cohort study of all calls taken by our maternal–fetal transfer service. Call logs were abstracted, and diagnoses, gestational ages, referring hospital, and mode of transportation were analyzed. The United States Health Resources and Services Administration's Medically Underserved Area (MUA) designations were used to identify hospitals in these areas. Geographic information system software was used to analyze and map geographic variables, including frequency of transfers from each hospital, distance traveled, mode of transfer, and MUAs. Results: From November 2012 to March 2017, there were 835 telephone consults without transfer and 1682 patients transferred from 103 hospitals. Preterm labor was the most common diagnosis ( n = 338, 20%), followed by hypertensive disorders ( n = 231, 14%). There were 738 transfers (44%) from MUAs, and 20 (19%) of hospitals were critical access hospitals, accounting for 121 (7%) transfers. One-way trips from a referring hospital accounted for 659 patients, and the transport team was dispatched in 1023 cases. The median distance traveled was 24 mi. For hospitals within 50 mi, the mean difference in transport time between air and ground was <1 h, yet there were 73 air round trips for hospitals <50 mi from our hospital. Conclusion: The transfer system is robust and supports underserved hospitals; however, the service could be deployed more efficiently.